Volatility and time series econometrics essays in honor of Robert Engle - Engle, R. F. (Robert F.); Watson, Mark W.; Bollerslev, Tim, 1958-; Russell, Jeffrey R. (Oxford : Oxford University Press, 2010)
This volume celebrates and develops the work of Nobel Laureate Robert Engle. It includes original contributions from some of the world's leading econometricians that further Engle's work in time series economics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Finance -- Econometric models; Econometrics; Time-series analysis